INTELLECTUAL CAPITAL OF ENTREPRENEURIAL STRUCTURES: ASSESSMENT OF RISKS AND DEVELOPMENT OPPORTUNITIES - Asaliev, A. M.; Orlova, L. N. (Интеллект. Инновации. Инвестиции, 2021)
The article examines the theory and practice of using intellectual capital as a source of development and formation of competitive advantages of entrepreneurial structures. The relevance of the study is associated with the overall increasing degree of use of intangible benefits that have a huge potential for growth and transformation. It can also be noted that against the background of the exhaustion of the resource model of development, intellectual capital is becoming an intensive growth factor. The aim of the study is to determine the possibilities for the development of entrepreneurial structures through the use of intellectual capital, as well as to identify the risks associated with intellectual entrepreneurial activity. The methodological basis of the study is the scientific works of famous scientists in the field of the knowledge economy, intellectual capital, digital economy, as well as the authors’ own early research. The main research methods were the methods of logical analysis, generalization, structuring, as well as the method of heat maps as a quantitative and qualitative method for assessing the risks of using intellectual capital, supplemented by expert and statistical methods. The empirical base of the study was data from open information resources, analytical agencies, and statistical materials. The subject of the research is the economic relations arising in the process of formation and use of intellectual capital by entrepreneurial structures. Particular attention in the article is paid to the theoretical and practical aspects of embedding the risk management methodology — ERM (Enterprise Risk Management) into the system of strategic management of intellectual capital, identification of the «red flags» of the organization’s business processes. The novelty of the presented research lies in determining the expanded structure of intellectual capital, the advantages of using intellectual capital for business structures, and highlighting the main stages of risk-based management of intellectual capital. The practical application of a risk-based approach to intellectual capital management is illustrated by the construction of a heat map of risks, which allows highlighting the most significant risks associated with the formation of employee competencies, stable trust relationships between the entrepreneurial structure, its counterparties and investors, and the state. As conclusions and recommendations, the authors present the directions of increasing the competitive advantages of a large entrepreneurial structure by integrating intellectual capital management processes into the development strategy and levelling the risks of its use.